The Digital Divide and Inequities for Students with Disabilities: Needed….A Bridge Over Troubled Waters! - Tyson, Patricia A. (Journal of the American Academy of Special Education Professionals, 2015)
One of the key concepts of the NCLB legislation was the improvement of student achievement in academics with the use of technology (NCLB, 2001). Ironically, the NCLB mandate of accountability has not provided the necessary resources for achieving its goals, and students with disabilities are, in fact, being left behind. Therefore, the law is intensifying the digital divide. The impact of legislative policies such as this on students with disabilities, while well intended, has led to barriers of access and equity that prevent teachers from effectively integrating the technology. The focus will be barriers to access and equity in types of special education technology, pedagogy and teacher training, and Universal Design for Learning. This paper will review relevant law, address implications of the digital divide on students with disabilities, and will conclude with recommendations for bridging the gap over the troubled waters of inequity and discrimination.